-2(6-10x)=1-(2x-6)

Simple and best practice solution for -2(6-10x)=1-(2x-6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(6-10x)=1-(2x-6) equation:


Simplifying
-2(6 + -10x) = 1 + -1(2x + -6)
(6 * -2 + -10x * -2) = 1 + -1(2x + -6)
(-12 + 20x) = 1 + -1(2x + -6)

Reorder the terms:
-12 + 20x = 1 + -1(-6 + 2x)
-12 + 20x = 1 + (-6 * -1 + 2x * -1)
-12 + 20x = 1 + (6 + -2x)

Combine like terms: 1 + 6 = 7
-12 + 20x = 7 + -2x

Solving
-12 + 20x = 7 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-12 + 20x + 2x = 7 + -2x + 2x

Combine like terms: 20x + 2x = 22x
-12 + 22x = 7 + -2x + 2x

Combine like terms: -2x + 2x = 0
-12 + 22x = 7 + 0
-12 + 22x = 7

Add '12' to each side of the equation.
-12 + 12 + 22x = 7 + 12

Combine like terms: -12 + 12 = 0
0 + 22x = 7 + 12
22x = 7 + 12

Combine like terms: 7 + 12 = 19
22x = 19

Divide each side by '22'.
x = 0.8636363636

Simplifying
x = 0.8636363636

See similar equations:

| 6=23 | | w^2-2w^2-8w-7=0 | | 15s=180 | | 1.03p-4=-2.15+8.72 | | -15+5x^2-3x+x^3=0 | | 12d-4=12d | | -0.6w=48 | | 4d=3d+2 | | 8x^2-18xy-5y^2=0 | | 6x^2+12x+12=0 | | 3(a+4)=36 | | -5=5(c-1) | | 10=-10+7m | | d+2=-4d-2 | | -2y=8x | | -(j+6)=-2 | | 4w^2=10w-13 | | 3x^2+18x+35=8 | | 7x+13=2x | | 10-p=8 | | 2x-4y=25 | | 1.5(2x-1)=0.75(x+1)-2 | | m^3+5=-2 | | -3+26-35z=-9 | | -3+26-35z=9 | | -3+26-35z=0 | | -3+26-35z=25 | | -3+26-35z=24 | | 121*5= | | -3a-2b=-3 | | 2(-7+6)=-16-7a | | V-3=-1 |

Equations solver categories